FACTORS CAUSING COMPLAINTS ABOUT UNETHICAL BEHAVIOR OF NURSES THAT OCCURRED WHILE PERFORMING DUTIES DUE TO THE RELATIONSHIPS OF INTERNAL AND INTER-DIMENSIONAL PHENOMENA - Jirapaet, Veena; Uthis, Penpaktr; Chaleoykitti, Saisamorn (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2020)
There are 3 key causal factors leading to complaints and professional misbehaviors: (1) Individual factors, mainly derive from practitioners’ mental and thinking process (active errors) e.g. forgetting, ignoring/neglecting, or lacking mindfulness. Importantly, such factors may also be caused by emotional quotient problems. Fifty six percentages of those committed cases were from professional misbehaviors under professional standards and service behaviors and offenses against other colleagues/ practitioners that involved loss of emotional self-control due to angry, for example, impolite verbal expression and violent behaviors. Next, (2) organization-related factors are the latent factors in the vulnerable work environment, in which patient safety issues can happen (latent errors). An important cause is the performance of duties in an organization where manpower management fails to comply with the standards of the Thailand Nursing and Midwifery Council on Nurse-Patient Ratio (ratio of not over 1:4). For example, the performance of afternoon shift duties in a medical ward at the nurse-patient ratio of 1:18, daily working hours exceeding 12 hours, and the need to work on the next day’s shift. Besides, the mixed manpower with vague job descriptions and organizational culture in taking oral medical instructions during non-emergencysituations were also found. Finally, (3) complainant factors which main motives for filing complaints are: (a) dissatisfaction with impolite/confronting communication behaviors, ignorance to service demands and threatening gestures upon the patient’s refusal to receive services, (b) dissatisfaction with the abuses in light of waste of time and money, violent behaviors, and fear of repeated acts, and (c) physical effects on patients/victims owing to unethical behaviors resulting in their suffering from critical conditions, need of long-term corrective treatment, permanent negative physical effects, or loss of life.